Perception of Academic Staff on Roles of Tertiary Institutions in Addressing Leadership Problems Facing Nigeria - Ogunode, Niyi Jacob; Daniel Omachoko Gabriel; Benjamin Dorcas Chogwu (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2023)
The aim of this paper is to assess the roles of tertiary institutions in addressing leadership  problems facing Nigeria. The study adopted a descriptive survey research design. The population is comprised of all academic staff in North-Central Nigeria. A total number of 400 sample sizes was used for the study. A stratified random sampling technique was used to select the sample size. A questionnaire was adopted as an instrument for data collection. The study concluded that the roles of tertiary institutions in addressing leadership problems facing Nigeria include; teaching leadership principles and styles via the GST programme and inculcation of best leadership styles and principles, carrying out research on causes of leadership failure, solutions to leadership problems, recommendations on models that suit Nigeria political structure. The paper recommended that the government at every level should involve the tertiary institutions in the running of government by engaging them to carry out research and provide technical support in law reforms and electoral acts amendment.